Gambaran kepercayaan diri terhadap harga diri pada wanita pekerja seksual di kecamatan baturraden - Antias Widia Asih; Siti Nurjanah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: To determine the relationship of female sex worker confidence in self-esteem in the Baturraden district.Methods: This research uses a quantitative method of descriptive analytical research. The sampling technique used in this study is accidental sampling. Respond in this study as many as 30 people.Results: The average selection of self-esteem before counseling increased self-confidence with self-esteem after self-confidence counseling was 4.54 with a p value = 0,000 (p-value <0.05).Conclusion: This study shows that there is a relationship of confidence in the self-esteem of women sex workers in the Baturraden district.